Vegetative growth and bean crop coefficient as related to accumulated growing-degree-days - Medeiros, Gerson Araujo de; Arruda, Flavio Bussmeyer; Sakai, Emílio; Fujiwara, Mamor; Boni, Newton Roberto (Pesquisa Agropecuaria Brasileira, 2000)
The vegetative growth and the crop coefficient (kc) for irrigated beans (Phaseolus vulgaris L.) was studied in relation to accumulated growing-degree-days (SG). A completely randomized design was used with three treatments and four replicates. Population density treatments were: crop sowed in evapotranspirometers at a density of 50 plants m-2 reduced to 25 plants m-2, when the canopy achieved full ground cover; and crop sowed with population densities of 14 and 28 plants m-2 in irrigated field. Crop growth was evaluated considering dry matter, vegetative ground cover and the leaf area index. All traits had a highly significant relationship to SG, even though plant density and water supply conditions affected them. The relationship between the basal crop coefficient (kcb) and SG was highly significant in the evapotranspirometers. In the field, the surface wetting after the rain or irrigation and the mild water deficits affected the correlations (r2) between kc and SG. The phenological events of the plants studied were not affected by the treatment, when related to accumulated growing-degree-days.